Influence of Inclusion of Different Levels of Okara Meal in Replacement of Groundnut Cake in the Diet on Nutrient Utilization and Growth Performance in Japanese Quails - Mahto, D. K.; Sinha, A. K.; Sinha, S. K.; Shivani, Swati; Ranjan, Rajeev (Indian Journal of Animal Nutrition, 2017)
The present experiment was conducted to study the effect of inclusion of different dietary levels of okara meal (soybean byproduct) replacing groundnut cake in Japanese quail ration on nutrient utilization and growth performance for six weeks. Two hundred commercial one week old Japanese quail chicks were randomly divided into four treatments. Each treatment had 5 replicates with 10 chicks each. Ground nut cake was replaced by okara meal in ration at 0, 25, 50 and 75% on protein equivalent basis in treatments T1, T2, T3 and T4, respectively. Total feed consumption was similar in all the four groups. The average total weight was higher (P<0.05) in T3 compared to other treatments. Feeding of graded levels of okara meal replacing groundnut cake at levels of either 25, 50 and 75 % in Japanese quails diets had no significant effect on feed conversion ratio and protein efficiency ratio compared with control group. The N retention was lower (P<0.05) in treatment T1 compared to other groups. The Ca retention was similar in all treatments whereas P retention was higher (P<0.05) in T3 compared to other groups. It was concluded that growth performance and nutrient utilization of quail chicks was best at 50% inclusion of okara meal replacing groundnut cake on protein equivalent basis.